The characteristics of dry eye syndrome patients in Wangaya Regional Hospital from April 2023 to April 2024 - Yuananda, A. A. A. S.; Dwipayani, N. M.; Wibawa, I. M. D. S. (International Journal of Advances in Medicine, 2025)
Background: Dry eye syndrome (DES) is a term used to describe a condition of the front of the eye that occurs in response to damage to the natural layer of tears that lines the front of the eye, called the tear film. Dry eye syndrome affects a person’s quality of life, especially when reading, watching, driving, and when using laptops or similar gadgets. Dry eye syndrome is one of the diseases that has the most frequent morbidity of ocular surface disease. The purpose of this study is to identify the characteristics of patients with dry eye syndrome at Wangaya Regional General Hospital, Denpasar on April 2023-April 2024 based on age, gender, occupation, medical history, medication history, and lifestyle. Methods: This is a quantitative study using purposive sampling technique to determine the participants. The data source in this study uses secondary data sources originating from medical records of dry eye syndrome patients who were treated at Wangaya Regional Hospital, Denpasar, Bali on April 2023-April 2024. This study enrolled 92 dry eye syndrome patients. Results: Of the 92 patients, 64 (69,6%) were ≥40 years old, 59 (64,2%) were female, 37 (40,2%) were private sector workers, 40 (43,5%) has history of hypertensions, 59 (64,1%) has no history of smoking or drinking alcohol. Conclusions: Most of dry eye syndrome patients were ≥40 years old, and most were female. Commonly the patient has history of hypertensions and has history of hypertensions medication. Most of the patients has no history of smoking or drinking alcohol.